2(3x − 7) + 18 = 10

I know how to do these mostly but after using the disrtibutive property I end up

with 6x -14 + 18 = 10 when using inverse operations what number should I use the -14 or the 18?

HiylinLink Feb 22, 2019

#1**+2 **

2(3x-7) + 18 = 10

6x-14+18 = 10

6x + (-14+18) = 10

6x + 4 = 10

6x + (4-4) = 10 -4

6x = 6

x = 1

ElectricPavlov Feb 22, 2019

#2**-4 **

Thank you so Much really apreciate it. So when I come across two numbers that do not have like terms I just add or subtract them then carry out the inverse operations?

HiylinLink Feb 22, 2019

#3**+1 **

Sorry...I am not sure what you mean by 'inverse operations'....... can you teach me what that means?

ElectricPavlov
Feb 22, 2019

#4**-4 **

Oh sorry, XD I ment you know like pemdas the order of operations but doing these equations they care reversed you do the weakest up to the strongetst point in the operation like addition or subtracting first then parenthases.

HiylinLink
Feb 22, 2019

#5**+1 **

Yes....I understand PEDMAS you must follow pedmas to solve these equations.....

ElectricPavlov
Feb 22, 2019

#6**-3 **

Yes just it can be done reversed.. or that's what my math lesson say's that it's like inversing the order of operations when solving equations like this.

Just like you have to follow PEMDAS to solve normal problems.

HiylinLink
Feb 22, 2019

#7**+1 **

'Like' inversing the order.....

First you have to deal with the parentheses......you cannot do the operation in the parentheses...so distributive property helps you deal with it.....

The you cannot really divide so the + and minuses must be done next and then the final division can actually be done....

so yah...it's kinda like PEDMAS in reverse....but I wouldn't memorize that.....just learn what you can and cannot do....

There are multiple ways to solve these type of equations....you COULD divide first:

2(3x-7)+ 18 = 10 Divide both sides of the equation by 2

(3x-7) + 9 = 5 Collect 'like ' terms

3x + (-7+9) = 5

3x + 2 = 5 divide everything by 3...just makes it more diff

x + 2/3 = 5/3 Subtract 2/3 from both sides

x = 5/3 - 2/3

x = 1

ElectricPavlov
Feb 22, 2019

#8**-3 **

Okay then, I reaally appreciate all the help you gave me for this I was really stumped so Thank you XD.

HiylinLink
Feb 22, 2019